The Relationship of Philosophy to Hegel’s Scientific Culture (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
This research explores the relationship between philosophy and science according to Hegel's philosophy, focusing on how the scientific nature of philosophy can be achieved through a comprehensive systematic framework. Hegel emphasizes that philosophical truth is only presented within an integrated logical system that reflects inclusivity and universality. The research examines the concept of philosophy as a science of the absolute idea and highlights Hegel's approach to connecting thought with reality through the notion of experience, which represents a pivotal point in understanding the relationship between philosophy and the sciences.The study has been revised to address its weaknesses by incorporating a critical perspective on Hegel's system compared to modern experimental sciences and clarifying the challenges his philosophy faces in light of contemporary scientific developments, including sciences that rely on statistical and probabilistic models. Additionally, a comparative discussion between Hegel and other philosophers, such as Kant and Nietzsche, has been introduced to broaden the analytical scope and highlight points of divergence among them.The research underscores the importance of Hegel's philosophy as a comprehensive framework for understanding the relationship between the particular and the universal, with a focus on the dialectical laws that drive thought and spirit towards self-realization in successive stages. It also discusses the distinction between philosophy and experimental sciences, referencing Hegel's principle of experience and how he addresses experimental subjects compared to reflective intellectual issues.The study concludes with a critical analysis of Hegel's contribution to linking reason with the absolute, recommending an expansion of Hegel's philosophy to include its applications in the humanities and social sciences, thereby enhancing its academic value in contemporary contexts.